2013
DOI: 10.1007/s11010-013-1588-8
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin attenuates vascular calcification in chronic renal failure rats

Abstract: Vascular calcification due to elevated phosphate levels is the major contributor of cardiovascular dysfunction. The oxidative stress and gene expression events modulate the transdifferentiation of vascular smooth muscle cells into osteogenic phenotype. This present study intends to evaluate the dose-dependent effect of diosgenin, an antioxidant on high phosphate induced vascular calcification in adenine-induced chronic renal failure rats. High phosphate environment causes elevated calcium accumulation with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
2
26
1
Order By: Relevance
“…Interestingly, Feere et al (2015) have shown that the liver histology was normal in an adenine-induced model of CKD, yet their data on the activity of two plasma enzymes, ALT and AST (measured as hepatic functions tests), indicated that the activities of these enzymes had been significantly inhibited four-and twofold, respectively, while the hepatic total CYP450 content was halved. Contrary to these data we have found, as well as others, that the activities of these plasma enzymes are elevated and not inhibited (Al Za'abi et al 2015, Kim et al 2013, Manivannan et al 2013. This probably indicates some tissue damage in the liver in adeninetreated rats, which is at variance with results obtained by Feere et al (2015).…”
Section: Discussioncontrasting
confidence: 93%
“…Interestingly, Feere et al (2015) have shown that the liver histology was normal in an adenine-induced model of CKD, yet their data on the activity of two plasma enzymes, ALT and AST (measured as hepatic functions tests), indicated that the activities of these enzymes had been significantly inhibited four-and twofold, respectively, while the hepatic total CYP450 content was halved. Contrary to these data we have found, as well as others, that the activities of these plasma enzymes are elevated and not inhibited (Al Za'abi et al 2015, Kim et al 2013, Manivannan et al 2013. This probably indicates some tissue damage in the liver in adeninetreated rats, which is at variance with results obtained by Feere et al (2015).…”
Section: Discussioncontrasting
confidence: 93%
“…The protective effect of gemigliptin on VC was independent of the level of serum phosphorus. Similarly, a previous report showed that the protective effect of diosgenin against VC depends on the direct action on VSMCs regardless of blood chemistry [28]. …”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that vascular calcification is strongly correlated with chronic renal failure . Manivannan et al established an animal model of vascular calcification in CRF by feeding the animals with a diet containing 0.75% adenine . In the present study, we established chronic renal failure in rats by gavage with adenine.…”
Section: Discussionmentioning
confidence: 68%